1998
DOI: 10.1046/j.1423-0410.1998.7430140.x
|View full text |Cite
|
Sign up to set email alerts
|

How Some Attitudes, Beliefs and Motivations of Spanish Blood Donors Evolve over Time

Abstract: With the passage of time, donors' attitudes and beliefs evolve in a way that is favourable to blood donation and their motivations remain stable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 31 publications
2
24
0
4
Order By: Relevance
“…[19–11132829] In the present study a small minority (5%) of nondonors stated fear as their reason for not donating blood. In Mombatho, donation was found to be a health risk and there was also uncertainty whether donating blood is safe.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…[19–11132829] In the present study a small minority (5%) of nondonors stated fear as their reason for not donating blood. In Mombatho, donation was found to be a health risk and there was also uncertainty whether donating blood is safe.…”
Section: Discussionmentioning
confidence: 53%
“…[927] Our donors are predominantly of young age groups (<30 yrs), and the positive motivational response from both donors and nondonors to token gifts was remarkable. Other than incentives, affective measures have frequently been shown to encourage blood donation; such measures include inducing a “sense of give” among the public, when presented with hypothetical emotionally charged situations dramatizing the need for donor blood,[2] “sense of solidarity or duty” and the possible personal or family benefits that donation might bring,[2829] feeling of satisfaction, being more alert and feeling generally better, after blood donation,[6] as well as a sense of sharing and willing to accept the export blood to benefit other local communities in need. [30] A recent report from Nigeria[11] found that 41% of donors prefer certificates as incentives for donation.…”
Section: Discussionmentioning
confidence: 99%
“…A study carried out among Dhaka University students in Bangladesh showed that only 16% of the donors ever donated voluntarily as physical harm and fear were found to be the common reasons for not donating 30. In Granada, fears deterred 32.3% from donating 31. The fear of becoming infected with HIV by donating blood was also a prevalent deterrent amongst the Scottish population, and this adversely affected their blood donation habit 32.…”
Section: Discussionmentioning
confidence: 99%
“…[17] Fernández MA et al (1996) observed that in donors group, 58.4% of female and 41.6% of males were there. [18] Boulware LE et al (2002) conclude their study with the finding that female, black race and fear of hospitals are three major factors negatively associated with prior history of blood donation. [19] Sebok et al (2007) reported disproportionately more women deferred in comparison to men.…”
Section: Discussionmentioning
confidence: 99%